Methodical Support for Conducting an Expert Research to Establish the Statute of Limitations for the Execution of Documents’ Requisites: Problems of Expert and Judicial Practice - M. V. Zhizhina; V. B. Danilovich (Теория и практика судебной экспертизы, 2022)
The article addresses the problems of methodical support for establishing the statute of limitations when conducting a forensic document examination, directly affecting the admissibility of an expert’s opinion as evidence in legal proceedings. Establishing the statute of limitations for the execution of documents’ requisites is one of the most demanded tasks when considering all categories of cases – administrative, arbitration, civil, criminal. Analysis of the forensic practice of this type of examination in legal proceedings shows the application of various methods and approaches. Such variety raises questions among both the judicial and legal communities. For example, what existing methods are scientifically substantiated, tested, certified, lead to reliable results, and can be used to solve expert tasks? Which are unsuitable for the use in expert practice, and for what reasons?To confirm the suitability of their author’s developments for forensic examination, individual non-state experts provide various patents and certificates. How legal and permissible is this practice?The article offers a competent analysis of the current situation on the example of the widely used method of “wet copying”